Zakat Management in Indonesia: a Legal Political Perspective - Imam Yahya (Faculty of Sharia and Law, Universitas Islam Negeri (UIN) Walisongo Semarang, 2020)
This article aims to describe the management of zakat in Indonesia in a political and legal perspective carried out by BAZNAS (Badan Amil Zakat Infaq and Sadaqah) and LAZ (Lembaga Amil Zakat). Management of zakat management in a political-law approach is manifested in the zakat management regulations in Indonesia, namely Law no. 23 of 2011 concerning Zakat Management. Through literature research with a political-law approach, this research finds the following three points. First, the existence of BAZNAS is legitimized by law as a non-structural institution under the President, which has the authority to manage zakat, whether it is the collection, distribution or development of zakat assets. Second, as a consequence, taxes that have been paid through central BAZNAS or regional BAZNAS can reduce taxable assets. Third, BAZNAS has the power to recommend LAZ as well as supervise LAZ's performance at all levels, and the results are reported to BAZNAS.